Analisis Pengkreditan Pajak Masukan pada PT. Batu Gunung Mulia Bersama Banjarbaru - Puspita Nurdelima; Noor Safrina; Salman, Putriana (P3M Politeknik Negeri Banjarmasin, 2025)
The era of increasingly tight business competition makes operational efficiency key for companies to maintain competitiveness and increase profitability. One significant component in the company's operational cost structure is tax, especially Value Added Tax (VAT). PT. Batu Gunung Mulia Bersama Banjarbaru, which is engaged in the field of cylinder repair services, faces problems in managing input taxes that are less than optimal, which can result in lost opportunities to credit the tax and increase overall operational costs. This study uses a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, which aim to understand the company's tax administration process and the factors that influence compliance with applicable tax regulations. The results of the study indicate that the company has carried out tax obligations in accordance with applicable regulations, but there are still obstacles in crediting input taxes due to lack of communication with the vendor. In addition, external factors such as tax socialization and internal factors such as understanding tax regulations also affect the level of company compliance.